Tindak Tutur Ilokusi dalam Interaksi Penjual dan Pembeli di Rumah Batik Cipaku - Ananda Puspakartika; Yanty Wirza; R. Dian Dia-an Muniroh (Departement of Mathematics Education, 2024)
Abstract The objective of this research is to identify the types and forms of illocutionary speech acts present in the interactions between sellers and buyers at Cipaku Batik House. The data employed in this study are conversations between sellers and buyers. The primary data source is comprised of 15 data sets. The qualitative descriptive method is employed in this research. The results indicate that there are five types of illocutionary speech acts in the interaction between sellers and buyers at Cipaku Batik House, as proposed by Searle. These are assertive, commissive, directive, expressive, and declarative. The stage with the highest frequency of occurrence is assertive, with 49.62% of the total occurrences (262). Directive speech follows with 19.88% (105). The data indicates that the frequency of occurrence of expressive speech is 123 times, representing 23.29% of the total. In contrast, commissive speech is present on five occasions, representing 0.95% of the total, while declarative speech is present on 33 occasions, representing 6.25% of the total. The sentence forms of illocutionary speech acts obtained in this conversation are declarative, imperative, and interrogative. The research focuses on the identification of the types and forms of illocutionary speech acts present in the interaction between sellers and buyers at Cipaku Batik House. Keywords: Sociopragmatics, Speech Acts, Illocution